A synthetic tryptophan metabolite reduces hemorrhagic area and inflammation after pulmonary radiofrequency ablation in rabbit nonneoplastic lungs. - Nakada, Hiroshi; Yamashita, Atsushi; Kuroki, Masaomi; Furukoji, Eiji; Uchino, Noriko; Asanuma, Taketoshi; Asada, Yujiro; Tamura, Shozo (Japanese Journal of Radiology, 2014)
Purpose: The purpose of this study was to determine the effect of a synthetic tryptophan metabolite, tranilast [N-(3,4-dimethoxycinnamoyl)-anthranilic acid], on inflammatory and hemorrhagic areas after pulmonary radiofrequency ablation (RFA) in rabbits.Materials and Methods: Percutaneous RFA using a 17-gauge LeVeen electrode was performed in normal rabbit lungs. The rabbits were divided into tranilast-treated (300 mg/kg/day, orally) and control groups (n = 24/group). The effects of tranilast were evaluated using multidetector-row computed tomography (CT), histology, and immunohistochemistry immediately after RFA on days 1, 7, 14, and 28.Results: Oral administration of tranilast significantly reduced the size of ablated lesions assessed using CT and histology on days 7 and 14. Furthermore, it reduced the hemorrhagic areas on day 7 and inflammatory areas on day 14, but did not affect the areas of coagulation necrosis on days 1, 7, 14, and 28. Immunohistochemical analysis showed an increase in the ratio of CD163-positive macrophage areas to rabbit macrophage (RAM11)-positive pan-macrophage areas and a decrease in the number of nuclear factor-κB-positive nuclei and CD31-positive microvessels in the tranilast group on days 7 and/or 14.Conclusions: The results suggest that tranilast modulates the repair process after pulmonary RFA through macrophage accumulation, suppression of inflammation, and angiogenesis.